2016
DOI: 10.1667/rr14035.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral Mitochondrial-Targeted GS-Nitroxide, JP4-039, Radioprotects Normal Tissue in Tumor-Bearing Radiosensitive Fancd2–/– (C57BL/6) Mice

Abstract: We evaluated normal tissue specific radioprotection of the oral cavity in radiosensitive Fanconi Anemia (FA) Fancd2−/−mice with orally established tumors using mitochondrial-targeted GS-nitroxide (JP4-039). Adult (10–12 weeks old) Fancd2+/+, Fancd2+/− and Fancd2−/− mice (C57BL/6 background) and subgroups with orally established TC-1 epithelial cell tumors received a single fraction of 28 Gy or four daily fractions of 8 Gy to the head and neck. Subgroups received JP4-039 in F15 emulsion (F15/JP4-039; 0.4 mg/mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 29 publications
9
58
0
Order By: Relevance
“…Other mitochondria-targeted agents, including derivatives of TEMPOL, were shown to protect against radiation-induced oxidative damage in normal cells and radiosensitize the glioma cells. 412,413,419,421 …”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 99%
“…Other mitochondria-targeted agents, including derivatives of TEMPOL, were shown to protect against radiation-induced oxidative damage in normal cells and radiosensitize the glioma cells. 412,413,419,421 …”
Section: Mitochondria-targeted Therapeutics In the Pre-clinical Momentioning
confidence: 99%
“…Patients with FA demonstrate evolution of acute myeloid leukemia resulting from the malignant transformation of bone marrow of hematopoietic stem cells (9). The use of the long-term bone marrow culture system mouse model of FA has a great potential value for elucidation of the sequential mutation mechanisms involved in evolution of hematopoietic malignancies (5)(6)(7). Further studies should elucidate the sequential mutational changes in Fancd2 −/− long-term bone marrow cultures and derived hematopoietic cell lines which lead to final malignant transformation by a single HPV or other viral or microbial factors including other oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several groups are studying the use of radiation protector agents. Animal models using FANCD2 −/− (FVB/N) mice, FANCD2 −/− (C57BL/6) mice, and FANCA −/− and FANCG −/− mice showed that the intraoral administration of JP4‐039 (GS‐nitroxide) before each radiation treatment improves local normal tissue radiosensitivity and distant bone marrow suppression. These results support the need for clinical trials with this agent for future use in clinical RT for patients with FA.…”
Section: Treatment Of Oscc In Famentioning
confidence: 99%